2022
DOI: 10.3390/cells11050830
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Anti-Ageing through Senescent Cells Specific Reprogramming

Abstract: In this review, we seek a novel strategy for establishing a rejuvenating microenvironment through senescent cells specific reprogramming. We suggest that partial reprogramming can produce a secretory phenotype that facilitates cellular rejuvenation. This strategy is desired for specific partial reprogramming under control to avoid tumour risk and organ failure due to loss of cellular identity. It also alleviates the chronic inflammatory state associated with ageing and secondary senescence in adjacent cells by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 116 publications
(234 reference statements)
1
7
0
Order By: Relevance
“…Moreover, hiPSCs derived from fibroblasts obtained from older patients no longer present abnormal nuclear morphologies and age-associated features such as DNA damage increased DNA methylation, increased reactive oxygen species, reduced levels of nuclear organization proteins or loss of heterochromatin markers (Horvath, 2013 ; Miller et al, 2013 ; Lo Sardo et al, 2017 ; Strässler et al, 2018 ). This confirmed prior research which suggested that biological age and developmental state are separable (Chen and Skutella, 2022 ). In contrast, the generation of human neurons by direct reprogramming of fibroblasts retains age-specific transcriptional profiles, keeping the reprogrammed cells at the same “biological age” as the donor cells (Mertens et al, 2015 ; Yang et al, 2015 ).…”
Section: Introductionsupporting
confidence: 89%
“…Moreover, hiPSCs derived from fibroblasts obtained from older patients no longer present abnormal nuclear morphologies and age-associated features such as DNA damage increased DNA methylation, increased reactive oxygen species, reduced levels of nuclear organization proteins or loss of heterochromatin markers (Horvath, 2013 ; Miller et al, 2013 ; Lo Sardo et al, 2017 ; Strässler et al, 2018 ). This confirmed prior research which suggested that biological age and developmental state are separable (Chen and Skutella, 2022 ). In contrast, the generation of human neurons by direct reprogramming of fibroblasts retains age-specific transcriptional profiles, keeping the reprogrammed cells at the same “biological age” as the donor cells (Mertens et al, 2015 ; Yang et al, 2015 ).…”
Section: Introductionsupporting
confidence: 89%
“…This is further supported by the recent p21-Cre line data [ 218 ] and the fact that the SASP from a small number of cells is sufficient to induce senescence in young mice and senolytic drugs induced a rejuvenation phenotype [ 278 ]. The next complicating issue is that the SASP is also not a homogenous cocktail of released factors but might highly differ in the composition of immunomodulatory factors and thus determine more physiological aging versus pro-inflammatory deteriorating phenotype (reviewed in [ 3 , 279 ]). Interestingly, different p16INK4A-positive cell elimination mouse models showed diverse phenotypes with the p16INK4A-INK-ATTAC model delaying aging phenotypes and increasing lifespan [ 72 ], while in the p16INK4A-3MR model wound healing was disturbed [ 41 ], and in p16INK4ACre;DTA mice liver fibrosis and reduced health-span were observed [ 39 ].…”
Section: Open Questions and Perspectivesmentioning
confidence: 99%
“…As p16INK4A expression is not an off–on phenomenon, but increases from embryonic stages until old age [ 38 ], in the next step it would be interesting to determine whether p16INK4A-expressing cells in the mouse models are eliminated at different levels of p16INK4A expression. If this is the case, sorting of the cells and secretome analysis could define the secretory phenotype of protective versus detrimental p16INK4A expressing cells which finally may serve as a rejuvenation approach in aged patients without the need and limitations of overexpression of reprogramming factors [ 279 ].…”
Section: Open Questions and Perspectivesmentioning
confidence: 99%
“…For a historic time line of major discoveries, we would like to refer to other review articles. [46][47][48]…”
Section: The Kinetics Of Rejuvenation Depends On the Administration O...mentioning
confidence: 99%